THE LEGACY OF THE HOCHSCHULE FÜR GESTALTUNG OF ULM FOR COMPUTATIONAL DESIGN RESEARCH IN ARCHITECTURE - NEVES, Isabel Clara (2013)
Abstract. Nowadays the use of computational design processes in architecture is a common practice which is currently recovering a set of theories connected to computer science that were developed in the 60s and 70s. Such pioneering explorations were marked by an interest in employing scientific principles and methodologies many developed in Research Centres located in the US and the UK. Looking into this period, this paper investigates the relevance of the German design school of the Hochschule für Gestaltung (HfG) Ulm to the birth of computation in architecture. Even thought there were no computers in the school. It is argued that the innovative pedagogies and some distinct professors have launched clear foundations that can be understood as being at the basis of further computational approaches in architecture. By describing and relating the singular work by Tomas Maldonado (educational project), Max Bense (information aesthetics) and Horst Rittel (scientific methods), this paper describes the emergence of analogical ways of computational design thinking. This analysis ultimately wishes to contribute for inscribing the HfG Ulm at the cultural and technological mapping of computation in architecture.